Pigeon Pie, Oh My! - Singleton, Debbie (New York Oxford University Press, 2013)
When one greedy goat strips a scarecrow bare, leaving a cornfield unprotected from five passing pigeons, it takes the gumption of Tiny Chick to save the day. She may be small but she's super smart and, with the help of her farmyard friends, she persuades those silly pigeons that they're about to be baked into a pie - it's enough to send them packing! Well, how would you like it if you turned up for an eat-as-much-as-you-like meal only to discover that you were on the menu? This funny farmyard drama shows that heroes can come in all shapes and sizes.
Include Colour Illustrations
Keywords: Pigeons -- Children's stories -- Domestic animals